Expansion of Prosodic Abilities at the Transition From Babble to Words: A Comparison Between Children With Cochlear Implants and Normally Hearing Children. Issue 4 (July 2017) - Pettinato, Michèle; Clerck, Ilke De; Verhoeven, Jo; Gillis, Steven
Abstract : Objectives: This longitudinal study examined the effect of emerging vocabulary production on the ability to produce the phonetic cues to prosodic prominence in babbled and lexical disyllables of infants with cochlear implants (CI) and normally hearing (NH) infants. Current research on typical language acquisition emphasizes the importance of vocabulary development for phonological and phonetic acquisition. Children with CI experience significant difficulties with the perception and production of prosody, and the role of possible top-down effects is, therefore, particularly relevant for this population. Design: Isolated disyllabic babble and first words were identified and segmented in longitudinal audio–video recordings and transcriptions for nine NH infants and nine infants with CI interacting with their parents. Monthly recordings were included from the onset of babbling until children had reached a cumulative vocabulary of 200 words. Three cues to prosodic prominence, fundamental frequency (f0), intensity, and duration, were measured in the vocalic portions of stand-alone disyllables. To represent the degree of prosodic differentiation between two syllables in an utterance, the raw values for intensity and duration were transformed to ratios, and for f0, a measure of the perceptual distance in semitones was derived. The degree of prosodic differentiation for disyllabic babble and words for each cue was compared between groups. In addition, group and individual tendencies on the types of stress patterns for babble and words were also examined. Results: The CI group had overall smaller pitch and intensity distances than the NH group. For the NH group, words had greater pitch and intensity distances than babbled disyllables. Especially for pitch distance, this was accompanied by a shift toward a more clearly expressed stress pattern that reflected the influence of the ambient language. For the CI group, the same expansion in words did not take place for pitch. For intensity, the CI group gave evidence of some increase of prosodic differentiation. The results for the duration measure showed evidence of utterance final lengthening in both groups. In words, the CI group significantly reduced durational differences between syllables so that a more even-timed, less differentiated pattern emerged. Conclusions: The onset of vocabulary production did not have the same facilitatory effect for the CI infants on the production of phonetic cues for prosody, especially for pitch. It was argued that the results for duration may reflect greater articulatory difficulties in words for the CI group than the NH group. It was suggested that the lack of clear top-down effects of the vocabulary in the CI group may be because of a lag in development caused by an initial lack of auditory stimulation, possibly compounded by the absence of auditory feedback during the babble phase. Abstract : Supplemental Digital Content is available in the text.